Tannin Loaded Nanoparticles and its Therapeutic Applications – A Comprehensive Review (Asian Journal of Pharmaceutics (AJP), 2021)
Cancer is one stage of a condition that occurs due to uncontrolled growth of cells and is caused by many factorsranging from genetic mutations to different lifestyle factors such as exposure to chemicals, radiation, tobaccousage, and physical exercise so on. They are so many surgeries and therapies treatment is available for cancer butthis treatment only reduces the symptoms of the disease, and complete cannot be expected. These chemical drugsare more prominent to destroy cancer cells in our body but they increase side effects includes nausea and vomitingit will lead to damage to the vital organs such as the kidney, heart, and lung. Phytoconstituents are one of thepromising treatment prospects for minimizing the side effects and to improve effectiveness of the chemotherapeuticdrugs and it is used for natural products, which have been traditionally used to treat many types of cancer. Manyplant extracts were described that pharmacological activities are characteristic of their phytoconstituents includestannins, flavonoids, saponin, alkaloids, and terpenes. Tannins are secondary metabolites of plants. Tannins arepopularly known as natural polyphenolic molecules possess many pharmacological actions such as antibacterial,anti-cancer, antioxidant, chemo-preventive, and anti-inflammatory actions. One of the problems that present theuse of tannins is their poor bioavailability. Nanoparticles have been introduced a different type of formulation andevaluation methods to identify their bioavailability of a drug. The present study concentrates on tannin-loadednanoformulations to increase the bioavailability in the treatment of cancer.